1999
DOI: 10.1103/physrevlett.83.500
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Shears Mechanism in Near-Spherical Tin Nuclei

Abstract: Lifetimes of states of a magnetic dipole band in each of the nuclei 106,108 Sn have been obtained using the Doppler shift attenuation method. The deduced B͑M1͒ transition rates show the characteristic behavior associated with the shears mechanism. A simplified semiclassical analysis yields B͑M1͒ values in qualitative agreement with those expected for previously assigned configurations. The results suggest extremely low deformations for these dipole structures. In particular, the 106 Sn band appears to be the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…Such bands have been observed in even-even 106,108 Sn [6,7], odd-A 105 Sn [8], and odd-odd 108 Sb [9]. In the odd-odd Sb isotopes, the yrast band of 108 Sb (N = 57) has been interpreted as the magnetic rotational band in terms of the tilted axis cranking (TAC) model [9].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Such bands have been observed in even-even 106,108 Sn [6,7], odd-A 105 Sn [8], and odd-odd 108 Sb [9]. In the odd-odd Sb isotopes, the yrast band of 108 Sb (N = 57) has been interpreted as the magnetic rotational band in terms of the tilted axis cranking (TAC) model [9].…”
mentioning
confidence: 98%
“…Another interesting area in this mass region is the phenomenon of shear bands. Such bands have been observed in even-even 106,108 Sn [6,7], odd-A 105 Sn [8], and odd-odd 108 Sb [9]. It is of particular interest to investigate the shear mechanism along an isotopic chain in this region.…”
mentioning
confidence: 99%
“…Indeed, the life time measurements indicated that the spin sequence form a stretched dipole band (B(M 1) ∼ 3 − 6µ 2 N ) and the E2 transition are almost missing (B(E2) ∼ 0.1(eb) 2 ). The decreasing behavior of the M1 strength with increasing spin was also experimentally confirmed [21,23,24]. The magnetic bands are characterized by quite unusual features:i) They are ∆I = 1 sequences of states of similar parity; ii) Despite the very low deformation, the energies follow the I(I + 1) rule; iii) The levels are linked by strong M1 transition rates with weak E2 crossover transitions (the typical B(M1)/B(E2) ratio ≤ 20 − 40(µ N /eb) 2 ); iv) the ratio J (2) /B(E2) is about an order of magnitude larger than that for normal or super-deformed bands.…”
Section: Magnetic Bandsmentioning
confidence: 61%
“…• High-spin states were populated in 136 Pm by the 105 Pd( 35 Cl,2p2n) reaction, where the 35 Cl beam was accelerated to 173 MeV [157]. The chiral-twin candidate bands earlier observed in 136 Pm, have been extended to high spins [ I= (21)], using the Gammasphere γ -ray spectrometer and the Microball charged-particle detector array. The rotational alignments and B(M 1)/B(E2) ratios confirm that both sequences have the πh 11/2 ⊗ νh 11/2 configuration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation